Economic Studies of Some Hydrogen Production Processes - Braga, Lúcia Bollini [UNESP]; Tuna, Celso Eduardo [UNESP]; Mayworm De Araujo, Fernando Henrique [UNESP]; Vane, Lucas Fachini [UNESP]; Pedroso, Daniel Travieso [UNESP]; Silveira, José Luz [UNESP] (Springer Nature, 2017)
There are more than ten methods for an economic analysis of energetic systems. Each researcher chooses their own suitable methodology. In the case of hydrogen production processes, there is the need to use a method that permits a comparison of the cost of hydrogen production considering all the processes studied in the previous chapter. The economic feasibility study was based on the methodology developed by Silveira and Gomes (1999), which allows evaluating the attractiveness of a project through assessing the costs of investment, operation, and maintenance of the system, resulting in the selection of the best option. In this chapter, it is determined the cost of hydrogen production per kWh of electricity produced (US$/kWh) for each process, and a study drawing a comparison of their cost is thereof presented on the basis of inputs being used and levels of investment.
Keywords: Annuity factor; Economic analysis; Economical comparison; Feasibility studies; Hydrogen cost; Interest rate; Maintenance cost; Operation cost; Operation time; Pay-back period